2003
DOI: 10.1111/1468-5957.05386
|View full text |Cite
|
Sign up to set email alerts
|

The Weekend and ‘Reverse’ Weekend Effects: An Analysis by Month of the Year, Week of the Month, and Industry

Abstract: In this paper, we examine whether the 'reverse' weekend effect recently documented by Brusa, Liu and Schulman (2000) is concentrated in a few industries or widely spread across all the industries. The findings in this paper indicate that the 'reverse' weekend effect exists not only in "broad" indices, but also in most "industries". The results suggest that the 'reverse' weekend effect may be driven by economic events that affect "all" industries, rather than "industry-specific factors". Although the patterns o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
1
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 22 publications
3
26
1
2
Order By: Relevance
“…This hypothesis is stronger than (1), i.e., (1) is necessary but not su¢ cient for (2). Therefore, if (2) is true, then so is (1).…”
Section: The Hypotheses Of Interest and Test Statisticsmentioning
confidence: 96%
See 1 more Smart Citation
“…This hypothesis is stronger than (1), i.e., (1) is necessary but not su¢ cient for (2). Therefore, if (2) is true, then so is (1).…”
Section: The Hypotheses Of Interest and Test Statisticsmentioning
confidence: 96%
“…The stochastic dominance rule is more satisfactory from an economic theory point of view than the commonly used mean-variance rule since it is de…ned with reference to a much larger class of utility functions/return distributions. 2 We …rst brie ‡y de…ne the criteria of stochastic dominance.…”
Section: Monday E¤ect and Stochastic Dominancementioning
confidence: 99%
“…A trend of researchers including Syed and Sadorsky (2006), Cho et al (2007) and Lim et al (2010) provide a reconfirmation of the weekend effect. However, others such as Brusa et al (2003) and Apolinario et al (2006) ignore it. In addition to that, Chan et al (2004) study showed that in capitals with a modest number of institutional holdings, the Monday seasonal is strong.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Sobre esta base, sugieren que el efecto lunes está impulsado por los inversores institucionales. Brusa et al (2003) también contradicen los hallazgos de Lakonishok y Maberly (1990) y, Abraham e Ikenberry (1994) quienes argumentan que la correlación significativa sólo se produce si las rentabilidades son negativas, no siendo así cuando sean positivas.…”
Section: Análisis Robustez Subperíodos Muestralesunclassified
“…Como se ha comentado en la revisión bibliográfica, en un gran número de trabajos se ha encontrado una correlación positiva entre las rentabilidades de los viernes y las de los lunes. Entre los que podemos destacar los de Chow et al (1997), Brusa et al (2003) o García (2007García ( , 2008) para los mercados españoles. Por ello se va a proceder a calcular el coeficiente de correlación entre las rentabilidades de los viernes con respecto a la de los lunes, para los cinco índices objeto de estudio, aplicando la siguiente expresión:…”
Section: Lunesunclassified